2021
DOI: 10.1016/j.dsx.2021.102302
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of post COVID-19 fatigue in patients with type 2 diabetes: A case-control study

Abstract: Background Post COVID-19 syndrome (PCS) has emerged as a major roadblock in the recovery of patients infected with SARS-CoV-2. Amongst many symptoms like myalgia, headache, cough, breathless; fatigue is one of the major symptoms which makes the patient severely debilitated. Research on PCS, in particular fatigue, in patients with diabetes has not been done. Methodology In this prospective study, we included patients with type 2 diabetes (T2D) who had COVID-19 infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…First investigations have shown that people with metabolic diseases may have a higher risk of developing long-COVID symptoms. Patients with T2DM having a COVID-19 infection had significantly more symptoms of fatigue after the acute illness as compared to those without diabetes [37].…”
Section: Presence Of Diabetes May Further Influence Long-covid Via Va...mentioning
confidence: 94%
“…First investigations have shown that people with metabolic diseases may have a higher risk of developing long-COVID symptoms. Patients with T2DM having a COVID-19 infection had significantly more symptoms of fatigue after the acute illness as compared to those without diabetes [37].…”
Section: Presence Of Diabetes May Further Influence Long-covid Via Va...mentioning
confidence: 94%
“…In a recent Cell paper, the authors demonstrated that T2D and high levels of acute SARS-CoV-2 RNAemia were strong predisposing risk factors for PASC ( Su et al, 2022 ; Vimercati et al, 2021 ). In another case–control study, patients with T2D who developed COVID-19 had a much greater likelihood of having high fatigue scores postinfection than those controls who were not infected ( Mittal et al, 2021 ). Moreover, patients with T2D had poorer grip strength post-COVID, and increased markers of inflammation relative to noninfected controls ( Su et al, 2022 ).…”
Section: Metabolic Dysfunction and Pascmentioning
confidence: 99%
“…The proportion of hyperglycemia among patients diagnosed with post-acute COVID-19 in our study was surprisingly high, which leads us to conclude that more aggressive glycemic control is required [ 31 ]. A two-way interaction between COVID-19 and diabetes has been recently evidenced, which involves a complex physiopathological characteristic underlying hyperglycemia and generally impaired glycometabolism.…”
Section: Discussionmentioning
confidence: 99%